PENGARUH PHYSICAL ENVIRONMENT TERHADAP REVISIT INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI MEDIASI - Ridwan Maf'ul Muttaqin (POLITEKNIK LP3I JAKARTA, 2024)
Using customer satisfaction as a mediator, this research analyzes how the physical environment influences the desire to revisit. This research uses quantitative methodology. Participants in this research were visitors to a modern theme-based cafe in the Sidoarjo DPR plot area. In this research, the sample consisted of one hundred respondents. The technique used in the sampling procedure is called purposive sampling. The survey delivery method via Google Form was used to collect respondent data, and a Likert scale was used to measure the instrument for each statement. The Partial Least Square (PLS) approach was then applied to field data using the SmartPLS version 4 program. Research findings show that there is a good and significant influence between Physical Environment and Customer Satisfaction. Physical Environment has a big impact on Revisit Intention. Revisit Intention is positively and significantly influenced by Customer Satisfaction. Through Customer Satisfaction, Physical Environment has a positive and significant influence on Revisit Intention Key words: Physical Environment, Revisit Intention, Customer Satisfaction.